Fenomena Hate Speech di Media Sosial dan Konstruk Sosial Masyarakat - Muhammad Arif Hidayatullah Bina (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2021)
The development of communication technology coupled with the proliferation of social media has changed the paradigm of communicating in today's society. The formation of a virtual society has also made it possible for humans to become whatever they want in cyberspace. Social media in this case has full control over the social reality of society. In the context of the syringe theory, this phenomenon shows that social media users are helpless in the face of a variety of social media content milling about on social media. This helplessness then becomes the potential for the formation of new social constructs in society. Like a double-edged knife, the convenience offered by social media also coincides with the emergence of new social problems such as hate speech and attitudes of intolerance that are expressed through the various content and features available on social media. Although only expressed through social media, hate speech and intolerance on social media also have an impact on the social life of the community and even form a new social reality and construct in society.